Perbandingan Penurunan Kadar Formalin pada Tahu yang Direbus dan Direndam Air Panas - akhmad muntaha; haitami haitami; Nurul hayati (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2015)
Tofu is a food with high protein content and the moisture content reaches 85%, so that it knows can not last long. Manufacturers know still use formaldehyde as a preservative. Handling to reduce formaldehyde levels in the know are soaked in hot water and boiled in boiling water. The purpose of this study was to determine the ratio decreased levels of formaldehyde in the know are boiled and soaked in hot water out. This type of research is True Experiment with posttest study design Only Control Group Design. The population in this study is tofu containing formalin. Then examined by spectrophotometry of formaldehyde levels in most groups as a pretest sample, others are given treatment and formalin levels checked by spectrophotometry. Data were analyzed using the Mann-Whitney test. Results of this study the average levels of formaldehyde in the know before the treatment is 68.668 ppm. Decreased levels of formaldehyde in formalin know after boiling for 10 minutes was 64.77%. Decreased levels of formaldehyde in formalin know with the treatment of immersion in hot water for 10 minutes is 33.1%. Based on statistical tests that have been conducted, it was found a significant difference between the reduced levels of formaldehyde in formalin boiled out and the know formalin soaked in hot water with sig. 0,000. Boiling know formalin reduce levels of formaldehyde greater than soaking out in hot water.